APPRECIATION OF SYARI’AH PRINCIPLES IN PROPERTY MANAGEMENT IN CONTEMPORARY MALAYSIA SOCIETY - Buang, Ahmad Hidayat (Jurnal Syariah, 2008)
With improving economic status of Muslims in Malaysia, especially in term of personal property and wealth acquisitions, problems and issues relating to the devolution of properties have risen. The main argument explaining these problems is the rejection of the modern property management model based on trust and will by Islamic fara’id rules. As the devolution of property after death based on fara’id rules as practiced in Malaysia is often a long, complicated and costly process, there is a need to formulate an Islamic model to avoid these difficulties. This is however not to say that the Islamic rules of fara’id should be discarded, since there are many other factors, such as legal framework, courts jurisdictions, administrative red tapes and societal attitude towards resolving disputes in estate distribution, also contributing significantly to the problem. In fact the rules of fara’id should be considered as a part of the wider spectrum of Syari’ah principles in property management in Islam. This article would propose hibah, in addition to wasiyyah and waqf, as a practical model of Islamic property management.